Metallothionein and cancer - Křížková, Soňa; Vaculovičová, Markéta; Adam, Vojtěch; Kizek, René (Journal of Metallomics and Nanotechnologies, 2015)
Metallothioneins (MT) are small (molecular weight in range 500 – 1400 Da) intracellular proteins rich in cysteine content. In humans four main isoforms of MTs have been discovered so far – MT-1, MT-2, MT-3 and MT-4. All of MTs functions – heavy metals binding, antioxidative, regulation and mmunomodulation are involved in MTs roles in cancer. MTs role is doubleedged in carcinogenesis; in healthy cells with high MT content it has protective effects, while in healthy cells with low MT content, carcinogenesis via environmental factors occurs, on the other hand, at cancer-transformed cell the high MT content increases the tumour malignancy and chemotherapeutics resistance. Expression of MT can be used as marker of tumour diseases. Increased level of MT in serum or full blood was found in many cancer diseases and can be used as early stage biomarker. To decrease tumour resistance, or on the other hand, to improve non-target cells tolerance to chemotherapeutic multiple approaches are tested, including specific increasing or decreasing of MT expression based on specific compounds or targeted gene therapy.
Keywords: metalothionein; nádorové proteiny; Neoplasm Proteins; Protein Isoforms; Metallothionein; nádory; chemorezistence; Drug Resistance, Neoplasm; Carcinogenesis; lidé; Neoplasms; Biomarkers, Tumor; protein - isoformy; nádorové biomarkery; Humans; karcinogeneze